Indagação Interdisciplinar no Pátio da Escola (IIPE): aproximações e distinções entre sua proposta e a educação popular freiriana - Santos, Ana Claudia Toledo Prado dos (2019)
The Interdisciplinary Inquiry in the School's Yard (IIPE) is a didactic-pedagogical proposal that intends to regard environmental issues at a local environment, the schoolyard. By its means, educators and students elaborate questions (inquiry) about the natural, social, and cultural environment and answer them by observing (action) and reflecting (reflexion). These are the three steps of the methodology used, called the inquiry cycle. For this research, we reflect on its principles and practices in the light of freirian popular education. For this, we analyze three documents elaborated by IIPE proponents and the following books by Paulo Freire: Pedagogy of the Oppressed, Pedagogy of Hope, Pedagogy of Autonomy and Learning to Question. In the quest for approximations and differences between IIPE and freirian pedagogy we found many compatibilities and few distinctions. Both approaches value the people's personal experience and reflection (students and teachers) as the educational process par excellence, as well as propose an active posture towards the world. We also investigate the potentialities and limitations of IIPE in the current school situation. Our objectives, in two schools in the city of São Carlos, SP, were: to promote the formation of teachers in the didactic-pedagogical proposal of IIPE; to elaborate and experience IIPE activities with educators and students in the current school situation; to reflect on the experience of these activities from our role as educators; to reflect on the potential and limits of IIPE for education in general and for environmental education. From pedagogical interventions, through the training of teachers and the accomplishment of activities with students, this study was based on action research. The teachers who attended the training became co-authors of this part of the research, by reflecting on the lived experiences. Several factors enabled the development of IIPE activities in schools and this research. The most relevant ones were the solicitude and commitment of the educators and the adequacy of the IIPE activities to the school curriculum. However, we identified crucial obstacles: the lack of time for joint work among educators to develop interdisciplinary activities and the limitations arising from the organization of school time; the tiredness of educators; the choice of themes according to the sequence of contents of the curriculum; the unwillingness for activities on the part of students; the higher than ordinary effort of students and educators; and the students self-confidence. For the viability of IIPE, we propose some changes. For schools we suggest: maximum limit of 50% of the educators' working time for interaction with students; reduction of the working day; valorization of the educators; less students per classroom; flexibility in the division of time (class duration, topics and contents in the curriculum); and promotion of activities in which students participate actively. For IIPE activities, we propose simpler and shorter activities, gradually increasing its complexity, and implementing the proposal for continuing education in IIPE in partnerships between schools and universities.